Improving english oral and public speaking skills in the classroom - López Montero, Rosberly (2019)
This paper describes the implementation of different techniques in the English class. Those techniques are taken and adapted from the methodology of Toastmasters International Club. The authors have adapted this methodology in order to improve their students’ English performance, which has proven to be effective in the foreign language classroom. Therefore, this paper details Toastmasters techniques in two groups of the Pacific Regional Center of University of Costa Rica: freshmen from the Major of English with Business Management Training and juniors from the English Teaching Major. The authors developed different techniques depending on the students’ level and course objectives and have concluded that this methodology can provide valuable resources to improveEnglish in the classroom.